The Role Of Teachers In Improving The Quality Of Learning In Madrasah Tsanawiyah - Usup Supriatna; Opan Arifudin; Ika Kartika (Yayasan Azka Hafidz Maulana, 2026)
This study aims to identify and describe the role of teachers in improving the quality of learning in Islamic junior high schools. The approach used was a qualitative case study method, involving in-depth interviews, observation, and documentation of teachers, students, and the principal. The results of the study indicate that teachers play a crucial role in creating a conducive, innovative, and quality-oriented learning environment. Teachers function not only as instructors but also as motivators, facilitators, and developers of student competencies. Furthermore, teachers' success in implementing various learning strategies, using a variety of media, and conducting ongoing professional development contribute to improving the quality of education in Islamic junior high schools. These findings are expected to serve as a reference in improving teacher quality and the quality of learning in Islamic junior high schools in general.